Determination of Urea Content in Dairy Cattle Feed by High Performance Liquid Chromatography via Refractive Index Detector: Method Optimization, Validation and Comparison with Spectro-Colorimetric Method - Umur, H; Hanoğlu Oral, H; Ekşi Karaağaç, H; Koçer, S; Uçurum, HÖ; Altınçekiç, E (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to analyze the urea content of Dairy Cattle Feed (DCF) using High Performance Liquid Chromatography via Refractive Index Detector (HPLC-RID), without derivatization, along with spectro-colorimetric method that is the official control method of European Union (EU). Towards that goal, the analysis procedure for the method was established, method optimization and validation were carried out by spiking urea at 2% level to DCF, which is the upper limit allowed for use in ruminant feeds in Türkiye. In method validation; R2: 0.9997 coefficient of determination at 25-100000 mg/kg linear range, 75 mg/kg limit of detection (LOD) and 250 mg/kg limit of quantification (LOQ), 1.08% repeatability RSD, 1.84% reproducibility RSD and 95.10% recovery were obtained. The applicability of the method was proven at 25-100000 mg/kg linear range with real samples by spiking 2% urea in Urea-Free Dairy Cattle Feed (UF-DCF), Low Urea Dairy Cattle Feed (LU-DCF), and High Urea Dairy Cattle Feed (HU-DCF). The presence of urea in UF-DCF was detected with the spectro-colorimetric (at 420 and 435 nm wavelength) method, while urea in UF-DCF was not detected by the in-house HPLC-RID method, (P<0.05). The amount of urea in LU-DCF without spiking urea was detected by the same level as HPLC-RID method and the SC-435 method (P>0.05). For HU-DCF blank samples, higher urea amounts were detected with the in-house HPLC-RID method as compared to the spectro-colorimetric methods used in the study (P<0.05). In DCF spiked with 2.0% urea, the urea amount found in the in-house HPLC-RID method were higher than that of the spectro-colorimetric method (P<0.05). As a result, the in-house HPLC-RID method that is developed in this study has shown great promise to be a potential, applicable and valid method for determining the urea amount in DCF.